Climate and famines: a historical reassessment. (May 2016) - Slavin, Philip
Abstract : This study, dealing with the question of the impact of climate and extreme weather events on famines, has two objectives. The first objective is to review recent literature on the topic, distinguishing between economic and political science papers aimed at addressing contemporary famine events in the Third World countries, and historical research dealing with famines of the past. The former category of literature is characterized by a tendency to take the connection between the two variables for granted. The latter category, however, tends to exercise more analytical caution, but it still exhibits a degree of environmental determinism. The second objective of the article is to reassess the role and impact of climate and short‐term weather anomalies on famines in pre‐Industrial societies, in both European and non‐European history. At first, it appears that famines went invariably hand‐in‐hand with climatic changes and anomalies. A closer analysis, however, reveals that those climatic events created environmental shocks (harvest failures and blights), which implied shortages, rather than famines. Whether those shortages were bound to transform into full‐fledged famines was determined by nonenvironmental factors: primarily, human institutions and demographic trends. Climate alone, it is argued, is incapable of creating famines. The often unquestioned connection between the two variables appears to be an imaginary cultural and political construct of our era, when the fear of global warming and the awareness of climate change dominate the public and scholarly discourse. WIREs Clim Change 2016, 7:433–447. doi: 10.1002/wcc.395 For further resources related to this article, please visit theWIREs website .